Особливості Національної гвардії України як суб’єкта правоохоронної діяльності - Музичук, О. М.; Muzychuk, O. M.; Чишко, К. О.; Chyshko, K. O.; Чишко Катерина Олександрівна (Право.ua. - 2023. -№ 1. - С. 231-237, 2023)
У статті наголошено, що характерними особливостями діяльності Національної гвардії України як суб’єкта правоохоронної діяльності є відмітні риси, що постають у ході діяльності НГ України в умовах актуальних соціально-економічних, політичних, безпекових викликів, зокрема у специфічному безпековому середовищі, сформованому в умовах воєнного стану. Дане середовище, породжене, у першу чергу, новітніми безпековими викликами, також охоплює цілий комплекс трансформацій на організаційно-управлінському та інституційному рівнях, деякі з яких тільки починають закладатися, але з огляду на свою принципову важливість та стратегічний характер також були розглянуті як окремі особливості.

The article emphasizes that the characteristic features of the activity of the National Security Service of Ukraine as a subject of law enforcement activities are the distinctive features that appear in the course of the activity of the National Security Service of Ukraine in the conditions of current socio-economic, political, security challenges, in particular, in the specifi c security environment formed in the conditions of martial law. This environment, created primarily by the latest security challenges, also encompasses a whole complex of transformations at the organizational, managerial and institutional levels, some of which are just beginning to be established, but given their fundamental importance and strategic nature, they were also considered as separate features. It is noted that the peculiarities of the National Security Agency of Ukraine as a subject of law enforcement activities include the adaptability of law enforcement activities of the National Security Agency of Ukraine, which implies readiness for frequent, unpredictable changes in the nature and directions of law enforcement activities; precautionary (preventive, preventive) activity of the National Security Service of Ukraine as an element of law enforcement activity; focus on building trust relations as a feature generated by the prevailing philosophy or organizational strategy of «community policing» embodied in domestic legislation; the inextricable connection between the law enforcement activities of the National Security Service of Ukraine and the sphere of strategic communications, which also embodies the vector for digitization, digitization, which are the basis of modern relations with the public. It was emphasized that on the basis of the identifi ed features, separate directions for improving the activity of the National Guard of Ukraine as a subject of law enforcement activity were formed, in particular, the development of information transparency as the basis of trust relations between the National Guard of Ukraine and the population in the fi eld of law enforcement activity; digitization and digitization of the activities of the National Security Service of Ukraine as a subject of law enforcement; increasing the competence of servicemen and employees of the National Security Service of Ukraine on issues of building an inclusive security environment; the use of a programmatic approach in the activities of the NG of Ukraine as a subject of law enforcement activities.

В статье отмечено, что характерными особенностями деятельности Национальной гвардии Украины как субъекта правоохранительной деятельности являются отличительные черты, возникающие в ходе деятельности НГ Украины в условиях актуальных социально-экономических, политических, вызовов безопасности, в частности в специфической среде, сформированной в условиях военной состояния.
Keywords: Національна гвардія України; National Guard of Ukraine; Україна; воєнний стан; умови воєнного стану; правоохоронна діяльність; Ukraine; martial law; law enforcement activities; Национальная гвардия Украины; Украина; военное положение; правоохранительная деятельность